2019
DOI: 10.1097/md.0000000000016401
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B and C prevalence and risk factors among young men presenting to the Brazilian Army

Abstract: Programa NacioNal de imuNizações (PNi): 40 aNos Programa NacioNal de imuNizações (PNi): 40 aNos Ministério da saúde secretaria de Vigilância em saúde departamento de Vigilância das doenças transmissíveis Brasília -DF • 2013

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 19 publications
1
10
1
Order By: Relevance
“…Viral hepatitis serologies, history of alcohol intake or co-medications use prior to hospital admission were not available. However, the prevalence rates of chronic hepatitis B and C are low in Brazil [ 22 , 23 ] and only four patients (1%) included in the present study reported any liver disease at admission. In addition, we considered aminotransferases levels collected at the first day of hospitalization to minimize the impact of long term COVID-19 or any hepatic drug induced toxicity during hospital stay.…”
Section: Discussionmentioning
confidence: 92%
“…Viral hepatitis serologies, history of alcohol intake or co-medications use prior to hospital admission were not available. However, the prevalence rates of chronic hepatitis B and C are low in Brazil [ 22 , 23 ] and only four patients (1%) included in the present study reported any liver disease at admission. In addition, we considered aminotransferases levels collected at the first day of hospitalization to minimize the impact of long term COVID-19 or any hepatic drug induced toxicity during hospital stay.…”
Section: Discussionmentioning
confidence: 92%
“…Among CKD patients, HBsAg positivity in DBS or serum was associated with infrequent condom use, which was also found among young men enlisted in the Brazilian Army, demonstrating the importance of health campaigns with a focus on condom use[ 19 ]. Anti-HBc positivity in serum and DBS was associated with shared nail cutters/razor/toothbrush and highlights the discussion of the role of manicurists in the transmission of HBV.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a study with a large number of young men from Brazilian army showed a prevalence of 0.18% of anti-HCV positivity. 25 The strategy of screening all individuals with more than 18 years in Brazil should be evaluated with caution and based on cost-effectiveness studies.…”
Section: Discussionmentioning
confidence: 99%